The Students’ Responses towards the Use of Procedure Genre to Make Workshop Manuals - Sri Hastuti (Jurnal Bahasa Inggris Terapan, 2019)
This study examined the students responses towards the use of procedure genre to make workshop manuals which was indicated by the result scores after being taught using procedure genre. Specifically, this study is aimed to know whether their response is positive or negative which is indicated by their scores. To do the study one class of 26 students of Civil Engineering Department of the Bandung State Polytechnic has been used as sample. The design of the research ist-test design, while the instruments for collecting the data are composition tests. Paired t-test was used to analyse the data to answer the research questions.The result of analysis using t-test is that the students’ responses towards the use of procedure genre to make workshop manuals are positive.The result of the test shows significant improvement of students’ competence after being taught. The result of the analysis answers the  research questions investigated in this study. It is expected that this study will give significant contribution to the teaching of writing text in the Polytechnic  Keywords: procedure genre, workshop manuals